CULTURAL INDUSTRIES AS INSTRUMENTS OF INTERCULTURALITY, IDENTITY COHESION AND DEVELOPMENT: GASTRONOMY AND TOURISM IN PERU - Tello Sierra, Joselyn Delia (2023)
This article seeks to demonstrate that cultural industries - tourism and gastronomy - can serve as instruments for strengthening and promoting interculturalism, social cohesion and development. It has an application mainly in urban-popular sectors (as confirmed in the interviews and surveys carried out) to influence the prevention and/or mitigation of conflicts of a cultural nature and due to social reproduction. In Peru, conflicts tend to be focused on and understood almost exclusively as those of a socio-environmental nature and linked to extractive activities. A broader vision allows us to understand that the conflict goes beyond the referred socio-environmental framework. Precisely, in the typology of conflicts described the causes that originate are based on exclusion, inequality, poverty, and the absence of opportunities (conflicts due to social reproduction) and discrimination, racism, inequity, inequality and exclusion, motivated by ethnic, linguistic and cultural reasons (cultural conflicts). Therefore, gastronomy and tourism, being cultural industries, as has been shown, instruments of social cohesion, interculturality and development, have an impact on creating the conditions to combat the structural causes of the conflict present in these cases, in the areas economic, social, cultural and socio-symbolic.